Pengembangan Model Evaluasi Kualitas Output Pembelajaran Teknik Komputer dan Jaringan di SMK Kota Padang - Melda Fajra; Ambiyar ambiyar; Fahmi Rizal; Oskah Dakhi; Wakhinuddin Simatupang (Cakrawala: Jurnal Pendidikan, 2020)
The purpose of this study was to develop an evaluation model of computer and network engineering learning program (EKOP) in SMK. The trial sample amounted to 402 respondents. Trials were conducted in several areas of the city of Padang. Data collection techniques implemented using the rating scale method and attitude inventory. The technique of analyzing data uses quantitative and qualitative approaches. Based on the analysis of the data obtained the results that can be concluded are: a). EKOP in computer and network engineering matches the data in the field; b). The EKOP evaluation model is excellent in the assessment of processes and results. This is based on the results and the assessment process of users, experts, and practitioners learning in computer and network techniques; and c). the assessment of users, experts and practitioners of computer engineering learning shows that the evaluation evaluation guidelines are quite good as a basis or reference for implementing the EKOP evaluation model in computer and network engineering in SMK; and d). EKOP models apply systematic and systemic thinking flow.